Influence of study in hee on ubiquity and strength of students’ computer gambling - M.D. Kudryavtsev; I.E. Kramida; V.A. Kuzmin; S.S. Iermakov; Miroslawa Cieslicka; Blazej Stankiewicz (Physical Education of Students)
Purpose: to clear up effectiveness of learning-education process for counteraction of students’ harmful passion to computer games’ ubiquity. Material: 1st - 3rd year students (main health group) were the objects of the research. In total they were 952 boys and 523 girls. In 1st year students’ academic groups testing was carried out ant the beginning of academic year (October); in academic groups of 1st-3rd year students the testing was at the end of academic year (May). Results: it was found that among 1st year boy students ubiquity of computer gaming as well as time losses, connected with it are higher than among girl students. Educational process is not sufficiently effective in struggle against computer gaming. For girls, this passion is not dangerous in general. In the course of study at HEE, the strength of this passion reduces independent on sex. Conclusions: for increase of educational process’s effectiveness and improvement of students’ life quality it is necessary to consider personal features of boy students as well as to organize health related measures with the help of health related physical culture means.